Wednesday
March 22, 2017

Post a New Question

Posted by on Sunday, July 5, 2009 at 11:18pm.

Solve for
3x + 6Y - 9z = 3
5x - 7y + 10z = -4
11x +4y - 6z = 2

  • college algebra - , Sunday, July 5, 2009 at 11:32pm

    take the first equation, and the third equation.
    mulitiply the first by 2, and the third by 3.

    6x+12y-18z=6
    33x+12y-18z=6

    that implies that x is zero.
    then the first and second

    6y-9z=3
    -7y+10z=-4
    multply the first by 10, the second by 9
    60y-90z=30
    -63y+90z=-36
    add,
    -3y=6 or y=-2

    solve for z in any equation, check your answers.

  • college algebra - , Sunday, July 5, 2009 at 11:38pm

    Since you don't specify which method, let's use good ol' elimination.

    #1x2 ---> 6x+12y-18z=6
    #3x3 ---> 33x+12y-18z=6
    subtract, by luck both z and y disappear
    x = 0

    #2x3 ---> 15x-21y+30z=-12
    #3x5 ---> 55x+20y-30z=10
    add
    70x-y=-2 but x=0, so
    y = 2

    sub back into #3 to get z = 1

    x=0
    y=2
    z=1

  • college algebra - , Thursday, July 9, 2009 at 8:18pm

    2x^3(2x^2+4x+3)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question